Holiday destinations: Understanding the travel choices of Irish tourists - Seán Lyons; Karen Mayor; Richard S. J. Tol (The Economic and Social Research Institute (ESRI), 2007)
This paper uses a McFadden choice model to measure the importance of destination, household and seasonal characteristics on the tourism destination choices of Irish households. The analysis is based on quarterly survey data of Irish households' travel destinations between 2000 and 2006. In total, some 55 000 holiday trips were observed. Destination characteristics such as temperature, GDP and coastline are found to positively influence choice probabilities, while population density and distance have a negative effect on choice. Household specific characteristics such as the numbers of people over 60 and children in a household are found to be important. We also identify differences in preferences across seasons and a change over time of the effect of destination country GDP on Irish holiday destination choices.
Keywords: D12; L83; 330; International Tourism; Ireland; Demand Modelling; Urlaubsverhalten; Erholungsgebiet; Nachfrage; Internationaler Tourismus; Schätzung; Irland